DISTRIBUTION OF PLASMODIUM PARASITES CAUSING MALARIA AMONG LOCAL CHICKENS IN SALAHUDDIN PROVINCE , IRAQ. - Shader, M. M.; Akoob, A. Y. (The Iraqi Journal of Veterinary Medicine, 2021)
This study included two stages, the first one was as epidemiological study of malaria in the local chickens of variuos areas in Salahuddin province the infection rate was 3.16 % out of 433 samples taken. There was different blood stages of the parasite which are represented by trophzoites, schizonts and to less extent gametocytes. The second stage was the experimental study,which showed the ability of induction of infection (subinoculation technique). Prepatent period was represented by the presence of trophozoites m schizonts and gametocytes. The most important clinical signs was partial paralysis , dullness and emaciation. The pathological changes showed congestion and enlargement of liver and spleen. congestion of brain with absence of exo-erythrocytic mild lymphocytosis in the infected group. it was concluded the ability of diagnosis of avian malaria using human malaria antigen by the indirect fluorescence antibody technique.